2016
DOI: 10.1080/08039488.2016.1216595
|View full text |Cite
|
Sign up to set email alerts
|

IFNGR2 genetic polymorphism associated with sex-specific paranoid schizophrenia risk

Abstract: The IFNGR2Q64R polymorphism is correlated with male sex and paranoid schizophrenia. It is suggested that a chronic neuroinflammation may predispose to the paranoid schizophrenia development in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…The haplotype analysis not only confirmed the association between rs44536634 and SCZ, but also supported that rs44536634 allele A was associated with an increased risk of SCZ in females. Furthermore, our research provided an evidence to support the distinct molecular phenotypes of SCZ patients with different gender, as reported in previous studies (Ben Nejma et al, 2013;Jemli et al, 2017;Ramsey et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The haplotype analysis not only confirmed the association between rs44536634 and SCZ, but also supported that rs44536634 allele A was associated with an increased risk of SCZ in females. Furthermore, our research provided an evidence to support the distinct molecular phenotypes of SCZ patients with different gender, as reported in previous studies (Ben Nejma et al, 2013;Jemli et al, 2017;Ramsey et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…A study conducted by Oumaima et al indicated that minor alleles of SNPs in genes LTA and TNFA were over-represented in male SCZ patients but not in female schizophrenia patients (Inoubli et al, 2018). Jemli et al (2017) researched the association between the functional polymorphism of IFNGR2 with SCZ and found the IFNGR2 Q64R polymorphism was associated with SCZ in males. The study conducted by Yang et al (2016) showed that the genotypes and allele distributions of rs3087494 in PLA2G12A were significantly associated with SCZ in males, but not in females.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the potential neuropathological contributions of IFNg have not escaped attention. Polymorphisms in the IFNg gene and its receptor were recently associated with the development of schizophrenia (Jemli et al, 2016;H.J. Kim et al, 2012;Paul-Samojedny et al, 2011) and acute manifestations of the disease have been correlated with decreased levels of IFNg (Arolt et al, 2000).…”
Section: Neuropsychiatric Alterationsmentioning
confidence: 99%
“…A study conducted by Oumaima et al indicated that minor alleles of SNPs in genes LTA and TNFA were over-represented in male schizophrenia patients but not in female schizophrenia patients (Inoubli et al 2018). Jemli et al researched Manuscript to be reviewed polymorphism was associated with schizophrenia in males (Jemli et al 2017). The study conducted by Yang Guang et.al showed that the genotypes and allele distributions of rs3087494 in PLA2G12A were significantly associated with schizophrenia in males, but not in females (Yang et al 2016).…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%
“…Furthermore, our research provided an evidence to support the distinct molecular phenotypes of schizophrenia patients with different gender, as reported in previous studies. (Ben Nejma et al 2013;Jemli et al 2017;Ramsey et al 2013).…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%